EKOLOGI BUDAYA DAN NILAI KEARIFAN LOKAL POHON SAGU DALAM DIMENSI MASYARAKAT SUKU TOLAKI - Sabaruddin Sinapoy; Basrin Melamba; Herman Herman (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Sinapoy, S., Melamba, B., & Herman. (2021). Ekologi budaya dan nilai kearifan lokal pohon sagu dalam dimensi masyarakat suku Tolaki. ETNOREFLIKA: Jurnal Sosial Dan Budaya, 10(3), 323–342. https://doi.org/10.33772/etnoreflika.v10i3.1163 ABSTRACT Sago, as the identity of the indigenous people of the Tolaki tribe, besides having many values ​​and benefits also contains historical and philosophical values, so that the position of sago is very important to the life of the Tolaki ethnicity in Southeast Sulawesi. Philosophical values ​​contained in sago plants/trees are the values ​​of local wisdom related to its relationship with culture and the environment called cultural ecology. Local wisdom in cultural ecology for the indigenous people of the Tolaki tribe is always interconnected to the